Kansai Japanese : the language of Osaka, Kyoto, and Western Japan - Tse, Peter (Tuttle language library, 1993)
Finally, a systematic approach to learning the language of Kansai's boardrooms, shops, bars, a and boudoirs. "Kansai time Out Kansai Japanese contains everything you need to know about Kansai-ben, the most important dialect of the Japanese language. Spoken in the Kansai region, which includes the well-known cities of Kyoto, Osaka, and Kobe, Kansai-ben has long been considered a cryptic dialect even by Japanese. Thus it is no wonder that foreigners who speak only standard Japanese are baffled when they find themselves surrounded by the 21 million Japanese speaking the Kansai dialect. Kansai-ben is said to be earthier and more direct than standard Japanese, but it has its own system of polite language that is not taught in books or schools. In fact, Kansai-ben is rarely taught anywhere, and until now there has been no English text that explains the workings of this colorful dialect. Entertaining and very practical, Kansai Japanese has hundreds of sample sentences and dialogues with both English and standard-Japanese equivalents, covering topics like: Traditional Kyoto dialect, Male and female speech, Lovers' language, Kansai honorifics land insults, TV and movie samurai language.